HMGCR and ApoE mutations may cause different responses to lipid lowering statin therapy - Kirac, D.; Bayam, E.; Dagdelen, M.; Gezmis, H.; Sarikaya, S.; Pala, S.; Altunok, E. C.; Genc, E. (Cellular and Molecular Biology, 2017)
Coronary artery disease (CAD) and its complications are the major causes of death in the world. Although statins have been used to lower lipid levels in CAD patients, this goal can not be attained in 1/3 of the patients. The objective of this study was to investigate whether common variations in HMG-CoA Reductase(HMGCR) and Apolipoprotein E (ApoE) genes involved in lipid and statin metabolism modify the effect of statins on serum lipid and lipoprotein concentrations in CAD patients.A hundred CAD patients were enrolled into the study. At the beginning of the study biochemical measurements were performed to determine the baseline levels performed. Patients were treated with 40 mg atorvastatin for 2 months and biochemical measurements were repeated. According to the post-treatment, LDL-c levels, patients were divided into 2 groups as non-responders and responders, respectively. The information regarding the risk factors such as smoking, alcohol consumption etc. were also obtained. DNA was isolated from peripheral blood. The presence of rs17244841 ve rs17238540 mutations in HMGCR and Îµ2, Îµ3 and Îµ4 variants of ApoE were determined by using RT-PCR. Results were evaluated statistically. HMGCR mutatations were mostly found in responders and Îµ4 variant of ApoE was mostly found in non-responders. It was also found that presence of HMGCR mutations causes a significant reduction in total cholesterol and LDL-c levels. Also presence of Îµ2 variant of ApoE causes a statistically significant increase in trigliseride levels. Our findings should be investigated with other researchers to clarify the mechanism.